An Evaluation of Prehospital Adenosine Use. (3rd April 2023) - Nelson, Alexander R.; Cone, David C.; Aydin, Ani; Burns, Kevin; Cicero, Mark X.; Couturier, Katherine; Rollins, Mark; Shapiro, Matthew; Joseph, Daniel
Abstract: Background: Adenosine has been safely used by paramedics for the treatment of stable supraventricular tachycardia since the mid-1990s. However, there continues to be variability in paramedics' ability to identify appropriate indications for adenosine administration. As the first of a planned series of studies aimed at improving the accuracy of SVT diagnosis and successful administration of adenosine by paramedics, this study details the current usage patterns of adenosine by paramedics. Methods: This cross-sectional retrospective study investigated adenosine use within a large northeast EMS region from January 1, 2019, through September 30, 2021. Excluding pediatric and duplicate case reports, we created a dataset containing patient age, sex, and vital signs before, during, and after adenosine administration; intravenous line location; and coded medical history from paramedic narrative documentation, including a history of atrial fibrillation, suspected arrhythmia diagnosis, and effect of adenosine. In cases with available prehospital electrocardiograms (EKGs) for review, two physicians independently coded the arrhythmia diagnosis and outcome of adenosine administration. Statistical analysis included interrater reliability with Cohen's kappa statistic. Results: One hundred eighty-three cases were included for final analysis, 84 did not have a documented EKG for review. Categorization of presenting rhythms in these cases occurred by a physician reviewing EMS narrative and documentation. Forty of these 84 cases (48%) were adjudicated as SVT likely, 32 (38%) as SVT unlikely and 12 (14%) as uncategorized due to lack of supporting documentation. Of the 99 cases with EKGs available to review, there was substantial agreement of arrhythmia diagnosis interpretation between physician reviewers (Cohen's kappa 0.77–1.0); 54 cases were adjudicated as SVT by two physician reviewers. Other identified cardiac rhythms included atrial fibrillation (16), sinus tachycardia (11), and ventricular tachycardia (2). Adenosine cardioversion occurred in 47 of the 99 cases with EKGs available for physician review (47.5%). Adenosine cardioversion was also deemed to occur in 87% (47/54) of cases when the EKG rhythm was physician adjudicated SVT. Conclusions: This study supports the use of adenosine as a prehospital treatment for SVT while highlighting the need for continued efforts to improve paramedics' identification and management of tachyarrhythmias.